Hak dan Kewajiban Kreditor Memiliki Hak Retensi dalam Pembagian Harta Pailit Berdasarkan Hukum Perdata Indonesia - Jayadi, Hendri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Bankruptcy is a complete confiscation of the debtor's assets to end debtor-creditor conflicts or to ensure that these assets are divided equally among creditors. The purpose of this study is to examine how Indonesian civil law is used to analyze the rights and obligations of creditors with retention rights in the distribution of bankrupt assets. Research using the Systematic Literature Review method, found 15 articles that match the criteria, with search strings from 2013 to 2023. The results of the study show that Commercial Court Judges will grant Suspension of Debt Payment Obligations (PKPU) to debtors and creditors to facilitate negotiation of payment methods, both in whole or in part, including debt restructuring if necessary. Debtors are required to file for bankruptcy if they have more than two creditors and outstanding debt obligations. The bankruptcy petitioner only loses his civil rights to manage and control his assets; they retain their civil rights to engage in other civil acts. This grant is legally considered as part of the bankruptcy estate, managing third party assets and appointing third parties to act as attorneys in legal proceedings, debtors are still allowed to maintain their legal status. The implication of this research is to provide an overview of the rights and obligations of creditors with retention rights in the distribution of bankruptcy assets based on Indonesian civil law.